Are bedding materials a source of useful microorganisms for dairy cow and ewe milk? - Monsallier F.; Feutry F.; Bouton Y.; Convert T.; Verdier-Metz I.; Montel M.C. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
Milk microbial diversity contributes to the sensorial diversity of raw milk cheeses. The milking is an important step for milk inoculation through teat skin, biofilm on the milking machine, water, air and animal environment. This study aims at evaluating microbial count of bedding materials usual in dairy cow and ewe farms. Four bedding materials (straw, mat, grass, slatted floor) from 48 farms in four French mountain areas of PDO cheese production were studied. Bedding surfaces, teats and bulk milk were sampled in winter (housed full-time) and summer (pasture) for cows, and during the grazing season for ewes. Microbial groups were counted on five culture media. For housed animals the microbial count (95 to 99% of ripening bacteria) of bedding material for cow and ewe was similar. In ewe farms, all microbial levels were higher on straw bedding than on slatted floor, and ripening bacteria levels on teat surface and in milk were significantly the highest with straw. On cow pasture surface, the ripening bacteria were less dominant (62%) than in winter and Gram negative bacteria (22%), yeasts (9%) and moulds (7%) proportions were higher. The season and the type of bedding material had similar effect on the teat skin but not in the milk microbial counts. The microbial flows from bedding to teat and teat to milk must be better understood to advise dairy farmers suggesting microbial transfer between bedding and teats.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)